O envelhecimento na dança em revisão, 2000 a 2015 - Souza, Adriana Silva de (2016)
This study aims to analyze how the art of dancing has been use to bring back the autonomy and as a resource of empowerment for older people in the society. For this, as a metodological procedure it was used literature systemic review for the survey of brazilian academic productions, master´s and doctoral dissertation and scientific articles in the period of 2000 to 2015, using the keywords: dance, ageing, elderly and old age. It was found 160 scientific productions; of these, 21 are on the CAPES‟s database; 19 in BDTD; 20 in BVS; 82 in the Biblioteca Digital Vérsila; and 18 in Google Scholar. Of the 160 productions, we selected 32 (7 doctoral dissertation, 13 master‟s dissertation and 12 articles), mainly performed by physical therapists and physical educators, and 26 of them are in the health sector and only 6 in the humanities. Most productions were held in public institutions in the South and Southeast regions of the country. Of the 32 identified productions, 21 were made specifically by women, four by men and 7 by women and men together, and the largest number of publications occurred from 2011. A large portion of the publications used dance as a measurement instrument, ethnographic and therapeutic resources. Although the dance is used in most studies as the measuremtne instrument, it was observed by the researches not only as a non-pharmocological strategy to aid in the treatment of diseases or functional gains, but as an opportunity to redeem the quality of life of the practitioners as they acquire greater body awareness, understanding of self and the environment, having the feeling of well being and pleasure during and after practice. In the studies using dance as an ethnographic resource it was observed that the art of dance being worked prioritizing the social reintegration and positive self image, enabling the exercise of citizenship, the concept of autonomy and empowerment of the elderly without the stereotype that makes the old commonly , what is " sick and limited." Thus, this perspective allows visibility and optimization of mature bodies in dance, simultaneously expanding the universe of dance and oldest person in the process of ageing better